2017
DOI: 10.1186/s13673-017-0088-3
|View full text |Cite
|
Sign up to set email alerts
|

Transaction processing in consistency-aware user’s applications deployed on NoSQL databases

Abstract: NoSQL databases are capable of storing and processing big data which is characterized by various properties such as volume, variety and velocity. Such databases are used in a variety of user applications that need large volume of data which is highly available and efficiently accessible. But they do not enforce or require strong data consistency nor do they support transactions. This paper investigates into the transaction processing in consistency-aware applications hosted on MongoDB and Riak which are two re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…From the collected of 18 articles, we found 8 articles [8][9][10][11][12][13][14][15] that were related to general overview of NoSQL databases and Big Data, 5 articles [16][17][18][19][20] that discussed performance comparison and evaluation between different NoSQL databases, 2 articles [21][22] that were associated to NoSQL data model and classifying NoSQL databases based on the Consistency, Availability, tolerance of network Partition of database which is known as CAP theorem, [23] this research has concentrated on the storage aspect of cloud computing systems using NoSQL. Other two [24][25] study reported the SQL query condition transformation to any NoSQL based database using Espresso Heuristic algorithm and analyzed the effects of transaction on data consistency & efficiency. However, the outcomes of the 18 articles on NoSQL used in Big Data processing are summarized in Table 1.…”
Section: Descriptive Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…From the collected of 18 articles, we found 8 articles [8][9][10][11][12][13][14][15] that were related to general overview of NoSQL databases and Big Data, 5 articles [16][17][18][19][20] that discussed performance comparison and evaluation between different NoSQL databases, 2 articles [21][22] that were associated to NoSQL data model and classifying NoSQL databases based on the Consistency, Availability, tolerance of network Partition of database which is known as CAP theorem, [23] this research has concentrated on the storage aspect of cloud computing systems using NoSQL. Other two [24][25] study reported the SQL query condition transformation to any NoSQL based database using Espresso Heuristic algorithm and analyzed the effects of transaction on data consistency & efficiency. However, the outcomes of the 18 articles on NoSQL used in Big Data processing are summarized in Table 1.…”
Section: Descriptive Analysismentioning
confidence: 99%
“…This study describes the background basics characteristics data model of NoSQL [23] DB-Engine Ranking This research has concentrated on the storage aspect of cloud computing systems, in particular, NoSQL Databases [24][25] Transactional for MongoDB, Riak and NoSQL 's SQL condition based on Espresso Heuristic algorithm To analyzed the effects of transaction on data consistency and efficiency and SQL query condition transformation for any NoSQL Databases…”
Section: Descriptive Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper, we propose a path-based price tracking system for SCM based on blockchain and smart contracts. Many methods exist to manage data through the system [3][4][5]. The model proposed in this paper manages the information regarding the cost of the SCM using the Ethereum blockchain approach.…”
Section: Introductionmentioning
confidence: 99%